Enrichment of IGF-1R and PPARγ signalling pathways in orbital inflammatory diseases: steps toward understanding pathogenesis. Issue 7 (26th February 2021) - Verma, Rohan; Choi, Dongseok; Chen, Allison J; Harrington, Christina A; Wilson, David J; Grossniklaus, Hans E; Dailey, Roger A; Ng, John; Steele, Eric A; Planck, Stephen R; Korn, Bobby S; Kikkawa, Don; et al.
Abstract : Background: Orbital inflammatory disease (OID) encompasses a wide range of pathology including thyroid-associated orbitopathy (TAO), granulomatosis with polyangiitis (GPA), sarcoidosis and non-specific orbital inflammation (NSOI), accounting for up to 6% of orbital diseases. Understanding the underlying pathophysiology of OID can improve diagnosis and help target therapy. Aims: To test the hypothesis that shared signalling pathways are activated in different forms of OID. Methods: In this secondary analysis, pathway analysis was performed on the previously reported differentially expressed genes from orbital adipose tissue using patients with OID and healthy controls who were characterised by microarray. For the original publications, tissue specimens were collected from oculoplastic surgeons at 10 international centres representing four countries (USA, Canada, Australia and Saudi Arabia). Diagnoses were independently confirmed by two masked ocular pathologists (DJW, HEG). Gene expression profiling analysis was performed at the Oregon Health & Science University. Eighty-three participants were included: 25 with TAO, 6 with orbital GPA, 7 with orbital sarcoidosis, 25 with NSOI and 20 healthy controls. Results: Among the 83 subjects (mean (SD) age, 52.8 (18.3) years; 70% (n=58) female), those with OID demonstrated perturbation of the downstream gene expressions of the IGF-1R (MAPK/RAS/RAF/MEK/ERK and PI3K/Akt/mTOR pathways), peroxisome proliferator-activated receptor-γ (PPARγ), adipocytokine and AMPK signalling pathways compared with healthy controls. Specifically, GPA samples differed from controls in gene expression within the insulin-like growth factor-1 receptor (IGF-1R, PI3K-Akt (p=0.001), RAS (p=0.005)), PPARγ (p=0.002), adipocytokine (p=0.004) or AMPK (p=<0.001) pathways. TAO, sarcoidosis and NSOI samples were also found to have statistically significant differential gene expression in these pathways. Conclusions: Although OID includes a heterogenous group of pathologies, TAO, GPA, sarcoidosis and NSOI share enrichment of common gene signalling pathways, namely IGF-1R, PPARγ, adipocytokine and AMPK. Pathway analyses of gene expression suggest that other forms of orbital inflammation in addition to TAO may benefit from blockade of IGF-1R signalling pathways.